Lung function testing in adults with preferential nasal breathing. Issue 9 (September 1992) - Stanford, C F; Martin, B; Nicholls, D P; Watson, D
Abstract : Three adult patients with asthma with preferential nasal breathing were found to have a typical pattern of lung function test results with substantial between test variation. This condition can be identified as a cause of unsatisfactory performance in respiratory tests by observing the patient's reaction after the nostrils have been occluded.